2022
DOI: 10.1007/s00146-022-01531-x
|View full text |Cite|
|
Sign up to set email alerts
|

From the ground up: developing a practical ethical methodology for integrating AI into industry

Abstract: In this article we present a new approach to practical artificial intelligence (AI) ethics in heavy industry, which was developed in the context of an EU Horizons 2020 multi partner project. We begin with a review of the concept of Industry 4.0, discussing the limitations of the concept, and of iterative categorization of heavy industry generally, for a practical human centered ethical approach. We then proceed to an overview of actual and potential AI ethics approaches to heavy industry, suggesting that curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In comparison, AI chatbots will define the future of telehealth as they are predicted to remotely diagnose patients at a low cost [28,29]. Research reveals promising results of such technology use, with outcomes similar to face-to-face therapy [30,31]. However, studies have shown differing results in user acceptance of this technology.…”
Section: A Multi-industry Analysis Of the Future Use Of Ai Chatbotsmentioning
confidence: 99%
“…In comparison, AI chatbots will define the future of telehealth as they are predicted to remotely diagnose patients at a low cost [28,29]. Research reveals promising results of such technology use, with outcomes similar to face-to-face therapy [30,31]. However, studies have shown differing results in user acceptance of this technology.…”
Section: A Multi-industry Analysis Of the Future Use Of Ai Chatbotsmentioning
confidence: 99%